2022
DOI: 10.3390/jof8020116
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Incidence and Shifting Epidemiology of Candidemia in Greece: Results from the First Nationwide 10-Year Survey

Abstract: Globally, candidemia displays geographical variety in terms of epidemiology and incidence. In that respect, a nationwide Greek study was conducted, reporting the epidemiology of Candida bloodstream infections and susceptibility of isolates to antifungal agents providing evidence for empirical treatment. All microbiologically confirmed candidemia cases in patients hospitalized in 28 Greek centres during the period 2009–2018 were recorded. The study evaluated the incidence of infection/100,000 inhabitants, speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 98 publications
3
9
0
Order By: Relevance
“…The increased incidence of non -albicans Candida species detected in our study is consistent with comparable data previously reported from our ICU [ 32 ] and elsewhere [ 19 ], as well as with recent data demonstrating an increasing incidence of candidemia in a nationwide study from Greece, with a species shift towards C. parapsilosis [ 33 ]. The increased incidence of non -albicans Candida species is in accordance with an epidemiological shift across the globe, including the emergence of non -albicans Candida species.…”
Section: Discussionsupporting
confidence: 93%
“…The increased incidence of non -albicans Candida species detected in our study is consistent with comparable data previously reported from our ICU [ 32 ] and elsewhere [ 19 ], as well as with recent data demonstrating an increasing incidence of candidemia in a nationwide study from Greece, with a species shift towards C. parapsilosis [ 33 ]. The increased incidence of non -albicans Candida species is in accordance with an epidemiological shift across the globe, including the emergence of non -albicans Candida species.…”
Section: Discussionsupporting
confidence: 93%
“…The most commonly reported Candida species with clinical importance in human is relatively finite. The World Health Organization (WHO) have concerned to develop a priority pathogen list for fungal ailments of public health important and to define research and development priorities to enhance innovation for new drugs, diagnostics and strategies (Galia et al, 2022).The most common clinical isolates of Candida species include Candida albicans, Candida tropicalis, Candida glabrata, Candida parapsilosis, Candida krusei, Candida dubliniesis and Candida guilliermondii respectively, and was consistent to the studies conducted by Mamali et al (2022). Mohandas and Ballal (2011) reported that 70.0% of Candida bloodstream infections were caused by biofilmforming agents.…”
Section: Discussionsupporting
confidence: 68%
“…Despite C. albicans is still the most frequently isolated species, a progressive shift to NAC spp. is recently reported in most parts of the world 17 . Furthermore, species distribution might be affected by the kinds of antifungal drugs empirically used.…”
Section: Discussionmentioning
confidence: 88%